Determinação sérica de haptoglobina, ceruloplasmina, alpha(1)-glicoproteína ácida, transferrina e alpha(1)-antitripsina, em equinos com cólica - Di Filippo, Paula Alessandra; Nogueira, Andressa Francisca da Silva [UNESP]; Santana, Aureo Evangelista [UNESP] (Universidade Federal de Santa Maria (UFSM), 2011)
Forty six equines were examined, 6 were healthy (G1) and 40 with colic, submitted to laparotomy. Twenty were showing lesions on the large intestine (G2) and 20 lesions on the small intestine (G3). The serum concentrations of acute phase proteins: haptoglobin, ceruloplasmin, antitrypsin, transferrin, and α- acid glycoprotein before and until 7 days after laparotomy. After centrifugation and fractioning of the samples, the acute phase proteins were individualized by electrophoresis on polyacrylamide gel containing SDS-PAGE, and the concentrations were determined by computerized densitometry. The increase was verified on the levels of acute phase proteins from animals with colic, before and after laparotomy, however with higher levels, premature and persistent on animals from G3. The results were due to the process of intestinal inflammation, caused by enteric injury and indicate that the serum protein profile can assist the identifying of the obstructed bowel segment and consequently the elaboration of the prognosis of horses with colic.
Determination of serum haptoglobin, ceruloplasmin, alpha(1)-acid glycoprotein, transferrin and alpha(1)-antitrypsin in colic horses
Keywords: Acute abdomen; Horse; Laparotomy